The Influence of Company Size, Audit Quality, Profitability, and Audit Committee on the Timeliness of Financial Report Submission (Study on Coal Mining Companies Listed on the Idx for the 2021-2023 Period) - Kaylee Milano; Riadi; Jeannette Patricia; Debi Masri (Britain International for Academic Research (BIAR-Publisher), 2024)
This study aims to analyze the influence of Company Size, Audit Quality, Profitability, and Audit Committee on the timeliness of financial report submission. The research method uses a quantitative approach. The population used in this research are companies listed on the coal mining index on the Indonesia Stock Exchange in the 2021-2023 period. The research samples obtained were 23 coal mining sub-sector companies with 69 observations. The results of the research show that company size does not partially influence the timeliness of financial report submission. Audit quality partially has a negative and significant influence on the timeliness of financial report submission. Profitability partially has a positive and significant influence on the timeliness of submitting financial reports. The Audit Committee partially has no influence on the timeliness of financial report submission.